2017
DOI: 10.1121/1.5003809
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and streaming of speech sounds based on differences in interaural and spectral cues

Abstract: Differences in spatial cues, including interaural time differences (ITDs), interaural level differences (ILDs) and spectral cues, can lead to stream segregation of alternating noise bursts. It is unknown how effective such cues are for streaming sounds with realistic spectro-temporal variations. In particular, it is not known whether the high-frequency spectral cues associated with elevation remain sufficiently robust under such conditions. To answer these questions, sequences of consonant-vowel tokens were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…At this point, it remains an open question as to why listeners use a memory buffer scheme for fricatives but not for other speech sounds. However, given the difficulties in a reliability account, and the fact that fricative‐vowel syllables can stream (David et al., ,b), the vowel‐as‐organizer account may offer the most coherent account, particularly given converging evidence for that from other domains (Diehl et al., ). However, a definitive test of this awaits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it remains an open question as to why listeners use a memory buffer scheme for fricatives but not for other speech sounds. However, given the difficulties in a reliability account, and the fact that fricative‐vowel syllables can stream (David et al., ,b), the vowel‐as‐organizer account may offer the most coherent account, particularly given converging evidence for that from other domains (Diehl et al., ). However, a definitive test of this awaits.…”
Section: Discussionmentioning
confidence: 99%
“…Challenging this are a number of studies examining auditory streaming in sequences of fricative-vowel pairs. In these studies, FV syllables are heard as a sequence with two streams indicated by the fact that alternating syllables were spoken by different talkers (David, Lavandier, Grimault, & Oxenham, 2017b), or at different locations (David, Lavandier, Grimault, & Oxenham, 2017a). These have generally shown that listeners can group fricatives with their vowels into a single coherent stream.…”
Section: Is It Even Speech? Auditory Groupingmentioning
confidence: 99%
“…Challenging this are a number of streaming on fricative-vowel pairs. In these studies, FV syllables are heard as a sequence with two streams indicated by the fact that alternating syllables were spoken by different talkers (David, Lavandier, Grimault, & Oxenham, 2017b), or at different locations (David, Lavandier, Grimault, & Oxenham, 2017a). These have generally shown that listeners can group fricatives with their vowels into a single coherent stream.…”
Section: Contextmentioning
confidence: 99%
“…buffer strategy for fricatives but not for other speech sounds. However, given the difficulties in a reliability account, and the fact that fricative-vowel syllables can stream (David et al, 2017a(David et al, , 2017b, the vowel-as-organizer account may offer the most coherent account, particularly given converging evidence for that from other domains (Diehl et al, 1987). However, a definitive test of this awaits.…”
Section: Summary At This Point It Remains An Open Question As To Whmentioning
confidence: 99%
“…It is carried out based on the conjunction of multiple stimulus-features including pitch, timbre and temporal structure, with spatial cues such as ITD and ILD contributing as well albeit to a lesser degree (David et al, 2017; Snyder and Elhilali, 2017; Stainsby et al, 2011). Previous studies have shown that segregation of two competing speakers is relatively good, but that performance drops sharply as the number of concurrent speakers increase beyond two (Brungart et al, 2001; Humes et al, 2017; Rosen et al, 2013; Simpson and Cooke, 2005).…”
Section: Discussionmentioning
confidence: 99%